The role of extrapulmonary personalized factors in asthma control - L. V. Tribuntceva; A. V. Budnevsky; G. G. Prozorova; O. N. Choporov; S. A. Kozhevnikova; I. A. Olysheva (Сеченовский вестник)
Aim. To study in real clinical practice extrapulmonary personalized factors in patients with asthma depending on the presence or absence of obesity and to build a model of asthma control based on them.   Materials and methods. Cross-sectional study was performed in 7 outpatient centers and included 237 adult patients with bronchial asthma (mean age 52.6 ± 1.3 years). The patients were divided in groups according to body mass index (BMI): without obesity (BMI < 30 kg/m2) – 128 patients, with obesity (BMI ≥ 30 kg/m2) – 109 patients. Asthma control was assessed by Asthma Control Questionnaire-5, physical activity – by the motor activity questionnaire (ODA23+), physical activity motivation – by data from the questionnaire. A linear regression model was built with the inclusion of sex, smoking, BMI, physical activity to predict the level of asthma control. Elasticity coefficient Ej, β- and Δ-coefficients and their ranks were calculated.   Results. The distribution of patients according to the degree of asthma control differed statistically significantly in the groups: controlled, partially controlled and uncontrolled were 25.8 %, 60.2 %, 14 % and 0 %, 33.9 %, 66.1 %, respectively, in groups without obesity and obese (p < 0.001). High or moderate physical activity was present in 88 % of non-obese and 47% of obese patients (p < 0.05). No differences were found in the motivation for physical activity: 41% with obesity and 42 % without obesity belonged to the category of “thinking about or trying to exercise”. In the regression model, the ranks were distributed as follows (the sum of the ranks of the coefficients Ej, β, and Δ is calculated) rank 1 – BMI (0.8857, 0.4163, 0.5429), rank 2 – level of physical activity (0.6489, 0.3497, 0.4467), rank 3 – smoking status (0.0339, 0.1333, 0.0047). The coefficient of the model was not significant for sex.   Conclusion. Obesity and low physical activity are the main personalized extrapulmonary factors that affect control of asthma. A significant part of the patients are motivated to modify their level of physical activity.